2023
DOI: 10.3991/ijet.v18i07.38701
|View full text |Cite
|
Sign up to set email alerts
|

Learning Outcomes of Civil Engineering Students in PBL Based on Building Information Modeling

Abstract: Abstract—The new technology called building information modeling (BIM) derived in China’s construction industry in the general background of information era, as well as construction of intelligent buildings and smart cities, requires many university students majoring in Civil Engineering who are skilled in BIM technology. Characterized by online learning at any time, free and diversified learning modes, and ubiquitous learning, project-based BIM teaching can effectively improve the learning outcomes of Civil E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Jianhua Ma's research explored the impact of PBL based on building information modeling on civil engineering students' learning outcomes. Their research found that by using BIM to build specific engineering cases, a positive learning experience could be provided, thereby improving students' academic performance and teamwork ability [2]. The research by Yi Huo et al focused on the impact of PBL-based virtual reality courses on the design abilities of preparatory teachers under the COVID-19 epidemic.…”
Section: Related Workmentioning
confidence: 99%
“…Jianhua Ma's research explored the impact of PBL based on building information modeling on civil engineering students' learning outcomes. Their research found that by using BIM to build specific engineering cases, a positive learning experience could be provided, thereby improving students' academic performance and teamwork ability [2]. The research by Yi Huo et al focused on the impact of PBL-based virtual reality courses on the design abilities of preparatory teachers under the COVID-19 epidemic.…”
Section: Related Workmentioning
confidence: 99%